PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BERBAGI PENGETAHUAN TERHADAP KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIS SISWA KELAS IX SMPN 14 PADANG - Sulastri, Yernita; Zulfaneti, Zulfaneti; febriana, Rian (STKIP PGRI Sumbar, 2014)
Â ABSTRACTThis research was conducted for the studentsâ lack of ability in mathematical thinking and mathematical communication, and for their low achievement in learning in class IX of SMPN 14 Padang. This research was intended to reveal whether the mathematical thinking and mathematical communication of the students taught by using Knowledge-Shared strategy was better than that of students taught by using conventional learning in class IX of SMPN 14 Padang. This was an experimental research. The instruments of the research were a questionnaire and a posttest on thinking and communication ability. The studentsâ learning achievement was seen from the result of the posttest. The result of data analysis indicated that the hypothesis of the research was accepted. Therefore, it was concluded that the mathematical thinking and mathematical communication of the students taught by using Knowledge-Shared strategy was better than that of students taught by using conventional learning in class IX of SMPN 14 Padang. In addition, based on the result of the questionnaire it was known that the studentsâ attitude toward the learning process by applying Knowledge-Shared strategy was in good category.